2008
DOI: 10.1021/ja077679s
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation Study of the Structural Stability and Materials Properties of DNA-Intercalated Layered Double Hydroxides

Abstract: The intercalation of DNA into layered double hydroxides (LDHs) has various applications, including drug delivery for gene therapy and origins of life studies. The nanoscale dimensions of the interlayer region make the exact conformation of the intercalated DNA difficult to elucidate experimentally. We use molecular dynamics techniques, performed on high performance supercomputing grids, to carry out large-scale simulations of double stranded, linear and plasmid DNA up to 480 base pairs in length intercalated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
136
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(163 citation statements)
references
References 72 publications
19
136
0
1
Order By: Relevance
“…Recently, the structural stability and material properties of DNA-intercalated LDH were examined by a computer simulation study based on molecular dynamics. [78] The structural models thus suggested were in good agreement with the experimental observations that anionic phosphate backbones aligned with aluminium hydroxide lattice, resulting in structural stability of DNA due to the hydration. The binding behaviour of DNA was also studied with flow cytometry, [79] and it was concluded that the anionic exchange capability of LDH could offer strong electrostatic interaction with DNA.…”
Section: Chemically and Biologically Stabilised Dna In Layered Nanopasupporting
confidence: 80%
“…Recently, the structural stability and material properties of DNA-intercalated LDH were examined by a computer simulation study based on molecular dynamics. [78] The structural models thus suggested were in good agreement with the experimental observations that anionic phosphate backbones aligned with aluminium hydroxide lattice, resulting in structural stability of DNA due to the hydration. The binding behaviour of DNA was also studied with flow cytometry, [79] and it was concluded that the anionic exchange capability of LDH could offer strong electrostatic interaction with DNA.…”
Section: Chemically and Biologically Stabilised Dna In Layered Nanopasupporting
confidence: 80%
“…3C) [54,55]. As a result of molecular dynamic modeling, it was found that the LDH layers are flexible enough to deform around bulky DNA molecules.…”
Section: Structural Features and Chemical Bonding Naturementioning
confidence: 99%
“…[34] To explain such structural compatibility, the conformation of DNA was found to match the interlayer topology with the phosphate backbone groups aligned with aluminum lattice positions. [35] Once again, the enhanced stability supplied by the organoceramic material is surmised to have played a key role in prebiotic evolution when the earliest life forms were exposed to harsh thermal conditions.…”
Section: From Biology To Materials and Vice-versamentioning
confidence: 99%